On A Simple Construction Of Triangle Centers X(8), X(197), X(K) & X(594) - Dasari Naga Vijay Krishna (Scientific Inquiry and Review, 2018)
In this article, we provide a new method for constructing the Nagel PointX(8) , Cevian quotient of Symmedian Point, Nagel Point X(197) and the isogonal conjugate of 1st Hatzipolakis-Yiu PointX(594). In addition, we also establish some collinearity and concurrence.